E-commerce in Romania during COVID-19 Pandemic - Maria GIRIP (Communications of International Proceedings, 2021)
Many people turned from the classical way of doing business to a more digital oriented one, where machines and AI are being used to serve both customer and producers’ needs. The internet and the online market make available for one’s business a new whole range of customers. What was reachable only within one’s geographical area or via distributors and other logistical solutions, now can be available online and reachable by a whole world that is using online shopping. Connecting vendors with customers with a single button, managing payments securely without the need to go to the bank, receiving products with the option of prescheduled deliveries, one-hour deliveries or no human contact delivery, made the online shopping the most flexible and accessible way to sell and buy products of any kind. This business model applies also to the small producers that this way found new clients and managed easier to adapt to market’s needs and gasp the demand. In current times, in Romania, rushed by the pandemic, many small producers were forced to change their business model towards an online one. This paper will analyze the benefits of switch towards an online business in Romania due to Covid-19 pandemics ’restrictions and related user behavior changes.
Keywords: commerce; online; covid-19